Nose to brain drug delivery: a recent update - Chatterjee, Bappaditya (OMICS International, 2017)
Drugs used to treat brain or central nervous system disorder suffer from shortfall of absorption and reaching brain due to blood brain barrier and cerebro spinal fluid barrier. Intra nasal administration of brain targeted drug delivery system is gaining popularity to circumvent blood brain barrier and enhance drug availability in brain. It also shows promising reduction of systemic adverse effect incurred by the drug. However there are major limitation of this route which restrict its success of application. Despite different dosage forms such as micro or nano emulsion, gel, in situ gel etc the intra nasal route is still lacking wide applicability. This short review aims to highlight some important features related to nose to brain drug delivery along with its potential challenges that need to overcome. It has focused on few interesting or significant articles on the matter published within last 4-5 years.